Improving Efficiency and Digital Literacy through a Web-Based Ordering System in PEM Akamigas Warehouse - Pratama, Rendy Bagus; Rahmadian, Rafli Ranu (Journal International Inspire Education Technology, 2025)
This research aims to design and develop a web-based material ordering information system for the Warehouse Laboratory of PEM Akamigas, which previously relied on manual recording methods that were vulnerable to errors, data duplication, and inefficiency. The study adopts an applied Research and Development (R&D) approach encompassing observation, interviews, document analysis, system design, prototyping using PHP and MySQL, and black box testing to ensure system functionality and reliability. The developed system integrates essential features, including user registration, product catalog browsing, order management, automated invoice generation, real-time stock updates, and comprehensive sales reporting, along with an administrative dashboard that facilitates data monitoring, improves decision-making accuracy, and enhances transparency between users and warehouse administrators. The implementation results demonstrate that the web-based system significantly increases data accuracy, reduces human error, and streamlines the ordering workflow, leading to more efficient operations. Furthermore, this innovation aligns with Industry 4.0 principles by promoting digital transformation in logistics education and strengthening the laboratory’s role as a learning facility that mirrors real-world warehouse operations, thereby improving students’ digital literacy, technical competence, and readiness for professional practice in the logistics and energy sectors.